Tinjauan Teologis Terhadap Pandemi Coronavirus Disease 2019 Dalam Prinsip Pembalasan - Efesus Suratman (Sekolah Tinggi Teologi Arastamar Bengkulu, 2021)
Many people expect a good, healthy, prosperous life, do not experience suffering. People who have a prosperous, healthy life, without suffering are usually identified with people who are obedient and fear God, where the concept of fearing God gets blessings and does not get curses, suffering, or other bad things that are often referred to as the principle of retaliation. This principle of retaliation is a common and believed principle from time to time. In wisdom literature, the principle of retaliation is one of the points that need attention. But in fact there are many who are pious, fearing God, whether they experience suffering that is not appropriate. This research approach is qualitative using a theological approach that can be used to understand the gaps that occur, collect data from various literary sources that can be used to collect the material needed, such as books in libraries, Junarl, the web, electronic mass media, etc. . the concept of the principle of retribution cannot be established in general terms and can be stated inaccurately if it is addressed to righteous people, pious people, good people, and suffering children, because the theory stated by the facts that occurs is incompatible and very contradictory.